Pengaruh Social Media Marketing, Content Creator, Dan Brand Awareness Terhadap Keputusan Pembelian Di Selak Kopi (Studi Kasus Generasi Z) - Liwa, Shochibul; Wahono, Budi; Wahyuningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2025)
Abstract With an emphasis on Generation Z, this study attempts to examine how TikTok Social media marketing, Content creators, and Brand awareness affect consumers' decisions to buy at Selak Kopi. The study uses a survey-based quantitative methodology. Questionnaires were given to Selak Kopi's Generation Z customers in order to gather data. Multiple linear regression was used to examine the connection between independent and dependent variables in the data. The findings show that Brand awareness, Content creators, and TikTok Social media marketing have a big impact on consumers' decisions to buy. These results demonstrate that TikTok and the role of Content creators in digital marketing strategies can increase Brand awareness and influence Generation Z's purchasing decisions. Keywords: Social media marketing, TikTok, Content creator, Brand awareness, Purchasing Decisions, Generation Z